Tracking quartz : a methodological approach to an elusive type of sources using chemical characterization according to their geological origin - Cattáneo, Gabriela Roxana (2018)
Fil: Cattáneo, Gabriela Roxana. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Departamento de Antropología; Argentina.